2022
DOI: 10.1108/jabs-02-2021-0066
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the switching intention of patients to e-health consultations platforms: blending inertia with push–pull–mooring framework

Abstract: Purpose Technology has revolutionized the delivery of health-care services, with e-consultations becoming popular mode of service delivery, especially during the pandemic. Extant research has examined the adoption of e-health consultation services, with little attention paid to examine the switching behavior. This study aims to identify factors affecting patients’ intentions to switch from conventional mode i.e. visiting hospitals/clinics to e-health consultations. Design/methodology/approach To understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 138 publications
0
10
0
Order By: Relevance
“…Previous literature on the PPM model has examined a handful of prominent push factors like low satisfaction, inconvenience, fatigue, perceived risk (Bansal, 2005; Dogra et al , 2022; Sun et al , 2017); pull factors like alternative attractiveness, enjoyment, autonomy, product quality (Dar and Xiongying, 2021; Guo et al , 2021; Ojiaku et al , 2018); and mooring factors like switching cost, consumer innovativeness, inertia, setup costs (Fu et al , 2021; Liao et al , 2019; Wang et al , 2019). Based on thorough review of literature, the current study identifies context-specific factors where satiation and perceived health risk are examined as push factors; economic benefit, home benefits and authentic experience are assessed as pull factors and trust, habit and subjective norms are examined as mooring factors as presented in Figure 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous literature on the PPM model has examined a handful of prominent push factors like low satisfaction, inconvenience, fatigue, perceived risk (Bansal, 2005; Dogra et al , 2022; Sun et al , 2017); pull factors like alternative attractiveness, enjoyment, autonomy, product quality (Dar and Xiongying, 2021; Guo et al , 2021; Ojiaku et al , 2018); and mooring factors like switching cost, consumer innovativeness, inertia, setup costs (Fu et al , 2021; Liao et al , 2019; Wang et al , 2019). Based on thorough review of literature, the current study identifies context-specific factors where satiation and perceived health risk are examined as push factors; economic benefit, home benefits and authentic experience are assessed as pull factors and trust, habit and subjective norms are examined as mooring factors as presented in Figure 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Telepresence is an essential feature of the web-based platform and describes a subjective immersive servicescape experience in a MMC platform, which can shape consumers' cognitive performance (Chen and Yao, 2022). The transition of the medical channel from physical to virtual is a challenge for patients (Dogra et al, 2022), but it is unknown how the virtual institutional environment based on a certain technology value proposition (Yang et al, 2021) can be relied on by consumers. In addition, Pool et al (2022) indicated that medical data security was connected with the degree of telemonitoring and surveillance.…”
Section: The Antecedents Of It Identitymentioning
confidence: 99%
“…Besides, grounded in trust theory, SOR theory or signal theory, a majority of current studies on MMC primarily explore how physician-related (Li et al, 2020a), technology-related (Dogra et al, 2022), self-related (Chen et al, 2022b;Wu et al, 2022a), third-party patient-related (Li et al, 2021), disease-related (Shah et al, 2021) factors influence consumer positively valenced engagement in MMC from patient-physician interaction perspective or patienttechnology interaction perspective. As the MMC platform is a technological bridge for doctorpatient interaction, uncovering the factors that influence consumer negative engagement in MMC from a patient-platform interaction lens is needed.…”
Section: It Identity and Consumer Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the healthcare sector, technology application concerning the various stakeholders is considered much important (Dogra, Bakshi, & Gupta, 2022). The Healthcare industry is considered a large and complicated industry that sometimes contains interactions among stakeholders which results in contradictory purposes and data issues (Dahleez, Bader, & Aboramadan, 2020).…”
Section: Introductionmentioning
confidence: 99%